Spatial vegetation patterns and neighborhood competition among woody plants in an East African savanna. Issue 2 (9th January 2017) - Dohn, Justin; Augustine, David J.; Hanan, Niall P.; Ratnam, Jayashree; Sankaran, Mahesh
Abstract: The majority of research on savanna vegetation dynamics has focused on the coexistence of woody and herbaceous vegetation. Interactions among woody plants in savannas are relatively poorly understood. We present data from a 10‐yr longitudinal study of spatially explicit growth patterns of woody vegetation in an East African savanna following exclusion of large herbivores and in the absence of fire. We examined plant spatial patterns and quantified the degree of competition among woody individuals. Woody plants in this semiarid savanna exhibit strongly clumped spatial distributions at scales of 1–5 m. However, analysis of woody plant growth rates relative to their conspecific and heterospecific neighbors revealed evidence for strong competitive interactions at neighborhood scales of up to 5 m for most woody plant species. Thus, woody plants were aggregated in clumps despite significantly decreased growth rates in close proximity to neighbors, indicating that the spatial distribution of woody plants in this region depends on dispersal and establishment processes rather than on competitive, density‐dependent mortality. However, our documentation of suppressive effects of woody plants on neighbors also suggests a potentially important role for tree‐tree competition in controlling vegetation structure and indicates that the balanced‐competition hypothesis may contribute to well‐known patterns in maximum tree cover across rainfall gradients in Africa.